Modeling of Texture and Starch Retrogradation of High-in-Fiber Bread Using Response Surface Methodology - Jarosław Wyrwisz; Małgorzata Moczkowska-Wyrwisz; Marcin A. Kurek (Applied Sciences)
The texture of bakery products is considered the most important trait for consumers, which needs to be explored in new products developed, such as high-in-fiber bread. This study aimed to develop models for texture attributes and starch retrogradation (based on initial enthalpy) as a function of porosity measured in non-complicated experimental processes—using Digital Imaging Analysis (DIA) of bread with various levels of dietary fiber (DF) content. Bread with high fiber content was prepared as the sample matrix by replacing part of the wheat flour with an oat fiber powder. The models for firmness, springiness, chewiness, cohesiveness, and enthalpy were developed using Response Surface Methodology (RSM), a robust statistical technique. Results indicated that the bread crumb’s firmness depended more on porosity than DF content. Models for each texture attribute were established and verified, and it was found that no significant difference (p < 0.05) existed between the predicted and measured values, confirming the validation of the models developed.